Parametric Investigation of Near End and Far End Crosstalks in Printed Circuit Board Lands - Md. Masud Rana; Md. Rabiul Islam; Md Kamal Hosain (International Journal of Electrical and Computer Engineering (IJECE), 2011)
Multi-conductor transmission line and interconnect carry signals with wide rage of frequencies from sending end to receiving end. The signal in one transmission line may be interupted by the unwanted contributions from the neighboring line conductors. If data speed increases, high frequency effects occur and the signals suffer from difficulties such as ringing, crosstalk, reflections, and ground bounce that seriously hamper the quality of the received signal. In order to estimate the signal quality, signal integrity analysis is needed. In this paper, an attempt has been made to investigate the sensitivity of the near and far end crosstalk on the parameters such as physical geometry of the conductors, electrical property of the substrate and the rise and fall time of excitation signal. The method of moments (MOM) is used to calculate the line parameters for different geometries. The simulation studies are carried out in TNT. The time domain and frequency domain analyses are performed using transmission line model of PSPICE. Moreover, a model is developed and tested in the laboratory. It is observed that the coupling inductance and capacitance vary with the variation of physical geometry and the substrate parameter.DOI:http://dx.doi.org/10.11591/ijece.v1i2.164